Bisphenol A and its analogues bisphenol S, bisphenol F and bisphenol AF induce oxidative stress and biomacromolecular damage in human granulosa KGN cells. (August 2020) - Huang, Mingquan; Liu, Shuang; Fu, Li; Jiang, Xue; Yang, Meng
Abstract: Bisphenol A (BPA) is gradually being replaced by presumably safer analogues such as bisphenol S (BPS), bisphenol F (BPF), and bisphenol AF (BPAF), due to its toxic, endocrine disrupting and possible carcinogenic effects. Although these bisphenols are widely used to produce a variety of everyday household items, the effects of BPA and its analogues on oxidative stress and cellular energy metabolism of the female reproductive system are still poorly understood. The aim of this study was to evaluate the oxidative stress, biomacromolecular damage and changes in calcium ion (Ca 2+ ) levels induced by BPA and its substitutes on KGN cells, which are maintain physiological characteristics of ovarian granulosa cells. We have observed that BPA and BPAF significantly reduced the viability of KGN cells, while BPS and BPF exhibited a slight toxic effect on the cells. The levels of intracellular ROS production and antioxidant capacity were significantly increased and decreased, respectively, in KGN cells after treatment with high concentrations of BPA and its analogues. In addition, we found that the damage to biomacromolecules, which are the main targets of oxidative stress was significantly increased after treatment with BPA, BPS, BPF, and BPAF. The intracellular Ca 2+ levels in KGN cells were significantly increased after exposure to high concentrations of BPA and BPAF, respectively. These results suggest that BPA and its analogues may play different roles in regulating the biologic functions of granulosa cells and the process of ovarian follicular development. Highlights: BPA and BPAF significantly reduced the viability of KGN cells. BPA and its analogues exposure break the balance of antioxidant system in KGN cells. BPAF induced the strongest oxidative damage to KGN cells. BPA and BPAF significantly increase intracellular calcium levels in KGN cells.